Blue Carbon Legal Reform in Indonesia: Institutionalizing Seagrass as a Critical Natural Capital - Raia Putri Noer Azzura; Achmad Gusman Catur Siswandi; Yulinda Adharani (Law Development Journal, 2026)
Blue carbon governance through Presidential Regulation No. 98/2021 and Ministry of Marine Affairs and Fisheries Regulation No. 1/2025 positions seagrass beds as essential carbon sinks for meeting Nationally Determined Contribution (NDC) targets. However, seagrass bed emission baselines have not been standardized within the National Registry System (SRN PPI) due to overlapping regulatory mandates. This situation is exacerbated by a normative antinomy: conservation instruments are sidelined by spatial planning regulations (the Job Creation Law and Government Regulation No. 21/2021) that legalize the conversion of conservation zones for National Strategic Projects (PSN). Using a legal-normative approach, this study finds that these legal contradictions legitimize "Weak Sustainability," which assumes that natural capital is substitutable. This legal loophole triggers reversal risk, undermining the validity of NDC mitigation and enabling ocean grabbing. As a solution, this study recommends institutionalizing seagrass beds as Critical Natural Capital (CNC) at the statutory level to achieve Strong Sustainability. This status of being absolutely irreplaceable (non-substitutable) will tighten the requirements for PSN exemptions, necessitate cross-ministerial synchronization of Measurement, Reporting, and Verification (MRV) based on TACCC, and integrate High Quality Blue Carbon Principles through community-based conservation instruments (OECM) and Free, Prior, and Informed Consent (FPIC) to ensure the nation's ecological justice.Blue carbon governance through Presidential Regulation No. 98/2021 and Ministry of Marine Affairs and Fisheries Regulation No. 1/2025 positions seagrass beds as essential carbon sinks for meeting Nationally Determined Contribution (NDC) targets. However, seagrass bed emission baselines have not been standardized within the National Registry System (SRN PPI) due to overlapping regulatory mandates. This situation is exacerbated by a normative antinomy: conservation instruments are sidelined by spatial planning regulations (the Job Creation Law and Government Regulation No. 21/2021) that legalize the conversion of conservation zones for National Strategic Projects (PSN). Using a legal-normative approach, this study finds that these legal contradictions legitimize "Weak Sustainability," which assumes that natural capital is substitutable. This legal loophole triggers reversal risk, undermining the validity of NDC mitigation and enabling ocean grabbing. As a solution, this study recommends institutionalizing seagrass beds as Critical Natural Capital (CNC) at the statutory level to achieve Strong Sustainability. This status of being absolutely irreplaceable (non-substitutable) will tighten the requirements for PSN exemptions, necessitate cross-ministerial synchronization of Measurement, Reporting, and Verification (MRV) based on TACCC, and integrate High Quality Blue Carbon Principles through community-based conservation instruments (OECM) and Free, Prior, and Informed Consent (FPIC) to ensure the nation's ecological justice